Internationales Handelsrecht : Zeitschrift für das Recht des internationalen Warenkaufs und Warenvertriebs (Verlag Dr. Otto Schmidt, 1999)
IHR - International Commercial LawJournal for international purchase and distribution lawCommercial and distribution law - up to date, international and practice-oriented The IHR journal informs you dependable about the current developments in jurisdiction and practice concerning international commercial and distribution law.In the journal particular consideration is given to the CISG , to the Proposal for a Common European Sales Law of the European Commission from October 2011 as well as to practical legal issues on the law applicable to commercial agents .Law firms specialised in business law, company lawyers, legal departments, judges, chambers of industry and commerce, arbitrators, legal scholars and academics will benefit from practical essays , crucial court decisions and case notes provided by each issue of the IHR journal.